Microstructure and biodegradation performance of Mg–4Ca–1Zn based alloys after ultrasonic treatment and doping with nanodiamonds for biomedical applications - Marchenko, Ekaterina S.; Baigonakova, Gulsharat A.; Khrustalev, Anton P.; Zhukov, Ilya A.; Vorozhtsov, Alexander B.; Chekalkin, Timofey L.; Monogenov, Alexander N.; Garin, Alexander S.; Kim, Tae-Woo; Kang, Seung-Baik (Materials Chemistry and Physics)
This work aims to study microstructural features, phase composition, topology, surface potential, and the biodegradation performance of Mg–4Zn–1Ca-based alloys whose melts were ultrasonically (US) treated and doped with nanodiamonds (ND). The findings show a correlation between the ratio of the secondary phase segregated along the grain boundaries and the biodegradation rate in the RPMI-1640 synthetic culture medium. The fewer Ca2Mg6Zn3 phase fraction, the lower the biodegradation rate. Also, ND doping does not significantly affect the biodegradation rate. Intriguingly, the latter in the US-treated alloy was found to be noticeably inhibited due to a smoother topography and the presence of the fewest Ca2Mg6Zn3 phase fraction segregated along the grain boundaries. Further studies are needed to assess the biodegradable potential of the ND doped alloy, which melt was ultrasonically treated.